An opisthorchiid concept of the genus Liliatrema (Trematoda: Plagiorchiida: Opisthorchioidea): an unexpected systematic position. Issue 1 (8th September 2020) - Sokolov, Sergey; Frolov, Evgeniy; Novokreshchennykh, Semen; Atopkin, Dmitry
Abstract: Liliatrema is a small genus of trematodes consisting of two species. Its systematic position has long been debated, partly because of the confusing reports about the structure of male terminal genitalia. Here we test the phylogenetic position of the genus Liliatrema using data on complete 18S rRNA and partial 28S rRNA gene sequences obtained for Liliatrema skrjabini . We also provide a detailed description of terminal genitalia in adult specimens of L. sobolevi and metacercariae of both Liliatrema species. The results of the 28S rDNA-based phylogenetic analysis indicate that Liliatrema falls within a well-supported clade, which also includes Apophallus and traditional opisthorchiids. This clade, in turn, is nested within a well-supported clade, containing Euryhelmis, Cryptocotyle and Scaphanocephalus. In the 18S+8S rDNA analysis, Liliatrema appears as a sister-taxon to the Cryptocotyle + Euryhelmis group. The Liliatrema + ( Cryptocotyle + Euryhelmis ) clade is a well-supported sister-group to the traditional opisthorchiids. The morphology of the terminal genitalia of the liliatrematids also corresponds to that of the opisthorchioids. Thus, the results of our morphological and phylogenetic analyses favour an unexpected conclusion that the genus Liliatrema belongs to the Opisthorchioidea. We propose that the genera Liliatrema, Apophallus, Euryhelmis, Cryptocotyle and Scaphanocephalus belong, respectively, within the subfamilies Liliatrematinae, Apophallinae, Euryhelminthinae and Cryptocotylinae of the family Opisthorchiidae.